2012
DOI: 10.1126/science.1216557
|View full text |Cite
|
Sign up to set email alerts
|

Lin28b Reprograms Adult Bone Marrow Hematopoietic Progenitors to Mediate Fetal-Like Lymphopoiesis

Abstract: The immune system develops in waves during ontogeny, being initially populated by cells generated from fetal hematopoietic stem cells (HSCs) and later by cells derived from adult HSCs. Remarkably, the genetic programs that control these two distinct stem cell fates remain poorly understood. We report that Lin28b is specifically expressed in mouse and human fetal liver and thymus, but not in adult bone marrow or thymus. We demonstrate that ectopic expression of Lin28 reprograms hematopoietic stem/progenitor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
384
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(409 citation statements)
references
References 60 publications
25
384
0
Order By: Relevance
“…Recently, two studies have suggested that Lin28a/b reexpression can counteract the developmental decline in cell regeneration and tissue repair. In both cases, let-7 repression was necessary to mediate this effect, although let-7 repression alone was not sufficient to enhance tissue repair (58,59). To determine whether LIN28B reexpression might enhance SC plasticity, LIN28B was reexpressed in the late embryonic (E15.5) cochlea and the ability of SCs to generate new HCs in response to γ-secretase inhibitor treatment was analyzed in early postnatal (P2) cochlear explant cultures (Fig.…”
Section: Lin28b Overexpression Results In a Delay In Prosensory Cell mentioning
confidence: 99%
“…Recently, two studies have suggested that Lin28a/b reexpression can counteract the developmental decline in cell regeneration and tissue repair. In both cases, let-7 repression was necessary to mediate this effect, although let-7 repression alone was not sufficient to enhance tissue repair (58,59). To determine whether LIN28B reexpression might enhance SC plasticity, LIN28B was reexpressed in the late embryonic (E15.5) cochlea and the ability of SCs to generate new HCs in response to γ-secretase inhibitor treatment was analyzed in early postnatal (P2) cochlear explant cultures (Fig.…”
Section: Lin28b Overexpression Results In a Delay In Prosensory Cell mentioning
confidence: 99%
“…The mammalian genome encodes two homologues of the C. elegans lin-28 genes (LIN28A and LIN28B) (3,4), which may control gene expression by distinct molecular mechanisms (5). They are important in processes such as embryogenesis (6), skeletal myogenesis (7), germ cell development (8,9), neurogliogenesis (10,11), differentiation (12,13), lymphopoiesis (14), and glucose metabolism (15). Genome-wide association studies have implicated the LIN28B locus in controlling both height and the timing of menarche in humans (16 -20).…”
mentioning
confidence: 99%
“…Erythropoietin-treated CD45 + fibroblasts overexpressing Oct-4 generate erythroid cells expressing adult β-globin protein rather than embryonic ζ-globin [22] [23]. Although these two studies are not comparable because of distinct species, starting cells, and transcription factors, it can be concluded that such a route of dedifferentiation may not be the only one.…”
Section: Dedifferentiationmentioning
confidence: 84%